Hydrological control of As concentrations in Bangladesh groundwater - Stute, M.; Zheng, Y.; Schlosser, P.; Horneman, A.; Dhar, R. K.; Datta, Saugata; Hoque, M. A.; Seddique, A. A.; Shamsudduha, M.; Ahmed, K. M.; Van Geen, A. (My University, 2012)
The elevated arsenic (As) content of groundwater from wells across Bangladesh and several other South Asian countries is estimated to slowly poison at least 100 million people. The heterogeneous distribution of dissolved arsenic in the subsurface complicates understanding of its release from the sediment matrix into the groundwater, as well as the design of mitigation strategies. Using the tritium-helium (3H/3He) groundwater dating technique, we show that there is a linear correlation between groundwater age at depths <20 m and dissolved As concentration, with an average slope of 19 μg L−1 yr−1 (monitoring wells only). We propose that either the kinetics of As mobilization or the removal of As by groundwater flushing is the mechanism underlying this relationship. In either case, the spatial variability of As concentrations in the top 20 m of the shallow aquifers can to a large extent be attributed to groundwater age controlled by the hydrogeological heterogeneity in the local groundwater flow system.
Keywords: Arsenic; Bangladesh; Groundwater; Hydrological control; Tritium; Helium